(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article analyzes and looks for implementation models of population administration service policies at the Makassar City Population and Civil Registry Office. The indicators used in this study refer to the van Meter and van Horn models using six indicators: policy standards and objectives; resource; inter-organizational communication; characteristics of implementing agents; disposition of implementor; and economic, social and political conditions. By using a qualitative approach, this study shows that the implementation of population administration services at the Makassar City Population and Civil Registry Service is still not well implemented. Lack of communication and socialization to the community is the cause of their not being able to carry out their main tasks and functions properly. This study recommends the coordination variable in policy implementation, in order to measure the success or failure of the policy.